Demonstration of an anti‐hyperalgesic effect of a novel pan‐Trk inhibitor PF‐06273340 in a battery of human evoked pain models. (28th November 2017) - Loudon, Peter; Siebenga, Pieter; Gorman, Donal; Gore, Katrina; Dua, Pinky; van Amerongen, Guido; Hay, Justin L.; Groeneveld, Geert Jan; Butt, Richard P.
Abstract : Aim: Inhibitors of nerve growth factor (NGF) reduce pain in several chronic pain indications. NGF signals through tyrosine kinase receptors of the tropomyosin‐related kinase (Trk) family and the unrelated p75 receptor. PF‐06273340 is a small molecule inhibitor of Trks A, B and C that reduces pain in nonclinical models, and the present study aimed to investigate the pharmacodynamics of this first‐in‐class molecule in humans. Methods: A randomized, double‐blind, single‐dose, placebo‐ and active‐controlled five‐period crossover study was conducted in healthy human subjects (NCT02260947). Subjects received five treatments: PF‐06273340 50 mg, PF‐06273340 400 mg, pregabalin 300 mg, ibuprofen 600 mg and placebo. The five primary endpoints were the pain detection threshold for the thermal pain tests and the pain tolerance threshold for the cold pressor, electrical stair and pressure pain tests. The trial had predefined decision rules based on 95% confidence that the PF‐06273340 effect was better than that of placebo. Results: Twenty subjects entered the study, with 18 completing all five periods. The high dose of PF‐06273340 met the decision rules on the ultraviolet (UV) B skin thermal pain endpoint [least squares (LS) mean vs. placebo: 1.13, 95% confidence interval: 0.64–1.61], but not on the other four primary endpoints. The low dose did not meet the decision criteria for any of the five primary endpoints. Pregabalin (cold pressor and electrical stair tests) and ibuprofen (UVB thermal pain) showed significant analgesic effects on expected endpoints. Conclusions: The study demonstrated, for the first time, the translation of nonclinical effects into man in an inflammatory pain analgesic pharmacodynamic endpoint using a pan‐Trk inhibitor.